Mark, a Pauline theologian: a re-reading of the traditions of Jesus in the light of Paul's theology - Pérez i Díaz, Mar (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Title -- Preface -- Table of Contents -- Acronyms and abbreviations -- Introduction -- 1. Scope and rationale of the subject -- 2. Methodology -- 3. Structure of the work -- Chapter 1: History of research. Status quaestionis -- 1.1. Authors who deny any Paulinisms in the Gospel of Mark -- 1.2. Authors who advocate Paulinisms in the Gospel of Mark -- 1.3. Authors in favour of Marcan Paulinisms, but with some reluctance -- 1.4. Authors who defend Petrine and Pauline influence on Mark's Gospel -- 1.5. Conclusions -- Chapter 2: The structure of Mark's narrative -- 2.1. The Gospel of Mark and its structure -- 2.2. Structural reading key: Who is Jesus? -- 2.3. Proposed structure -- 2.3.1. First part of the Gospel of Mark -- 2.3.2. Second part of the Gospel of Mark -- 2.3.3. Conclusions -- Chapter 3: Pauline theological elements within the Gospel of Mark -- 3.1. The use of the word εὐαγγέλιον -- 3.2. The misunderstanding of those around Jesus -- 3.2.1. The family of Jesus -- 3.2.2. The disciples of Jesus -- 3.2.3. Conclusions -- 3.3. The question of the Law. The Marcan controversies and Paul -- 3.3.1. From Capernaum to Galilee: Mark 1.21-45 -- 3.3.2. The authority of Jesus before the Law: Mark 2.1-3.6 -- 3.3.3. First conclusions -- 3.3.4. The difficult question of purity -- 3.3.5. Second conclusions -- 3.3.6. Consequences and confirmation of the Pauline and Marcan conception of the Law -- 3.3.7. Conclusions on Paul's and Mark's understanding of the Law -- 3.4. The enigma of the two multiplications of the loaves in Mark -- 3.4.1. Importance of the broad and immediate context of Mark 6.34-44 and Mark 8.1-10. Marcan accents within the two stories. -- 3.4.2. Structure in parallel cycles -- 3.4.3. The Eucharistic tradition in Paul and Mark and the section of the loaves in Mark. -- 3.4.4. Conclusions -- 3.5. The mission to the pagans.